Modular Assembly of Allosteric MEK Inhibitor Structural Elements Unravels Potency and Feedback‐Modulation Handles. Issue 12 (6th November 2015) - Hartung, Ingo V.; Pühler, Florian; Neuhaus, Roland; Scholz, Arne; Siemeister, Gerhard; Geisler, Jens; Hillig, Roman C.; von Ahsen, Oliver; Hitchcock, Marion
Abstract: Having recently identified a so‐far unexplored area adjacent to the known binding site of allosteric mitogen‐activated protein kinase kinase (MEK) inhibitors, we now report an extension of these studies by combining our new side chains with different MEK inhibitor cores in a modular manner. Replacement of the amide headgroup with inverse sulfonamides resulted in the identification of new MEK inhibitors with at least 10‐fold higher cellular potency against K‐Ras‐mutated tumor cells. A selected inhibitor from this new series retained the favorable pharmacokinetic profile of its predecessor in rodent and non‐rodent species and displayed significant in vivo efficacy at once‐daily oral doses of 0.25–1 mg kg −1 in a K‐Ras‐mutated xenograft model. The brain penetration potential of this analogue was significantly attenuated relative to PD325901. In a second series, the central fluorophenyl core was replaced by a pyridine moiety which gave rise to a similar boost in cellular potency. Most notably, analogues from this second series do not show MEK feedback phosphorylation in K‐Ras‐mutated A549 cells. Our results complement recent reports on the structural intricacies of MEK–Raf feedback interactions. Abstract : Directed evolution of MEK inhibitors by backbone shuffling! Rational reassembly of mitogen‐activated protein kinase kinase (MEK) inhibitor structural elements in a gene‐shuffling‐like fashion gives rise to exceptionally potent and in vivo efficacious novel inhibitors which show low potential for brain penetration and do not induce MEK pathway reactivation.